Financial governance: Cases at Village-Owned Enterprises (BUMDEs) in Lampung Province - Ekawati, Evi; Sari, Yetri Martika (Goodwood Publishing, 2024)
Purpose: This study examines the accountability and transparency of BUMDes financial governance implementation in Lampung Province within four stages of the financial governance process, which results in BUMDes inactivity. Research methodology: This study uses a qualitative approach to analyze financial governance in BUMDes. The analysis is viewed from the four stages of village finance governance and indicators of transparency and accountability. Data collection was carried out through interviews with BUMDes administrators and distributing questionnaires. The resource persons in this study were BUMDes managers in Lampung Province. Results: This study affirms that while the financial governance process in BUMDes incorporates elements of transparency and accountability, the level of implementation is inadequate, resulting in inactive BUMDes in Lampung Province. Finance governance is carried out based on BUMDes management's needs and understanding without appropriate governing documentation. Additionally, this research highlights the necessity for community participation to be appropriately implemented. Limitations: The focus on village-owned enterprises in Lampung Province limits the generalizability of the study findings to other village-owned enterprises in other provinces. Contribution: This research provides insight into BUMDes financial governance, specifically the implementation of finance governance in Lampung Province. It also examines which parts of the four stages of the financial governance process need improvement and optimization to increase transparency and accountability of BUMDes, as well as decrease the number of inactive BUMDes. This is a previously unexplored topic of research that is relevant to all stakeholders concerned with BUMDes financial governance.